Personal and Task-Related Moderators of Leader-Member Exchange Among Software Developers. - Ozer, Muammer (Journal of Applied Psychology, 2008)
A study was conducted to test the moderating roles of personal—i.e., locus of control—and task-related—i.e., task autonomy—factors on leader-member exchange (LMX) relationships. Data were obtained from a sample of 287 software developers and 164 supervisors participating at a large international information technology exhibition. Findings revealed that the LMX-job performance relationship was stronger when employees' locus of control was internal as opposed to when it was external. Findings also indicated that the relationship was stronger when task autonomy was high as opposed to when it was low. Findings imply that, contrary to theoretical expectations, employees' locus of control did not moderate the LMX-job satisfaction relationship.